Hygiene and Business Management Training for Low-Grade Coffee Bean Mask Products in Ulubelu - Sri, Sri Hidayati; Nurullia Febriati; Fibra Nurainy; Haidawati; Silaturahmi Wiraputri; Prasetyo Hadi (Universitas Islam Negeri Raden Intan Lampung, 2026)
Ulubelu District, Tanggamus Regency, Lampung Province, is one of the robusta coffee-producing areas with considerable potential for local resource-based community enterprise development. At the end of the harvest season and during sorting, farmers often obtain low-grade coffee beans with limited market value. KWT Anggrek in Pekon Gunung Tiga has initiated the processing of low-grade coffee beans into herbal coffee mask products, but the group still requires stronger knowledge of hygienic production, business management, financial recording, product labeling, and licensing preparation. This community service activity aimed to improve the capacity of KWT members to produce coffee-based masks hygienically and to manage the product as a small household enterprise. The activity used a participatory training approach consisting of need identification, lectures, discussion, demonstration, hands-on practice, mentoring, and evaluation through pre-test, post-test, questioning, and practice observation. The results showed that participants improved their understanding of raw material selection, worker hygiene, equipment sanitation, clean production flow, packaging, storage, basic business planning, cost calculation, simple bookkeeping, product labeling, and licensing preparation. The evaluation indicated that participants' understanding reached up to 80% after the activity. This training strengthened local resource utilization and supported women's entrepreneurship in rural coffee-producing communities. Keywords: business management; coffee by-product; cosmetics hygiene; KWT Anggrek; training.